2009
DOI: 10.4049/jimmunol.182.2.851
|View full text |Cite
|
Sign up to set email alerts
|

The EBV-Encoded dUTPase Activates NF-κB through the TLR2 and MyD88-Dependent Signaling Pathway

Abstract: The innate immune response plays a key role as the primary host defense against invading pathogens including viruses. We have previously shown that treatment of human monocyte-derived macrophages with EBV-encoded dUTPase induces the expression of proinflammatory cytokines through the activation of NF-κB. However, the receptor responsible for EBV-encoded dUTPase-mediated biological effects is not known. In this study, we demonstrate that the purified EBV-encoded dUTPase activates NF-κB in a dose-dependent manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
162
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(169 citation statements)
references
References 62 publications
6
162
0
1
Order By: Relevance
“…2). Interestingly, it has recently been shown that the nonstructural EBV protein, dUTPase, is recognized by TLR2, leading to NF-kB activation (36). It is thus not surprising that we have observed that the virus efficiently downregulates both TLR2 and TLR9 mRNA, as both receptors are activated by two distinct EBV components, similarly to HSV-2 (37).…”
Section: Discussionmentioning
confidence: 64%
“…2). Interestingly, it has recently been shown that the nonstructural EBV protein, dUTPase, is recognized by TLR2, leading to NF-kB activation (36). It is thus not surprising that we have observed that the virus efficiently downregulates both TLR2 and TLR9 mRNA, as both receptors are activated by two distinct EBV components, similarly to HSV-2 (37).…”
Section: Discussionmentioning
confidence: 64%
“…It is reported that EBV BILF1 and BLLF3 proteins expressed in later stages of lytic replication again upregulate NF-B signaling (80,81). EBV G-protein-coupled receptor (EBV BILF1) also appeared to activate the NF-B pathway in COS-7 and Burkitt's lymphoma cells (82).…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory viruses that can activate TLR2 (29,63) also have been associated with MS exacerbations (31,32,61). In addition, EBV, which is strongly associated with MS susceptibility (30), is able to activate the transcription factor NF-kB and the production of the chemokine CCL2 in a TLR2-dependent manner (65,66).…”
Section: Foxp3mentioning
confidence: 99%